PREDICTION OF 35,000 ALL CLOTHES SALES RANGE USING WMA METHOD - Bella Syahputri; Adi Prijuna Lubis; Suci Andriyani (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2022)
Abstract: The 35,000 department store is a business engaged in the sale of clothes, having its address at Jalan Sisingamangaraja. Clothing is one of the basic human needs to protect and beautify themselves. The problem that occurs in the 35,000 department store is the difficulty of predicting the number of clothing sales, resulting in an accumulation of goods. The method used in this study is the Weighted Moving Average (WMA) forecasting method. The purpose of this study is to apply the Weighted Moving Average method to the forecasting system in determining clothing sales at 35,000 convenience stores. The results of the application of the Weighted Moving Average method to predict clothing sales that have been made, then get the prediction results for June 2022 using 3 weights totaling 203 Pcs with an error accuracy of 33.40% and prediction results for June 2022 using 6 weights totaling 220 Pcs with accuracy 34.31% error. The conclusion is that the Weighted Moving Average method can accurately predict clothing sales at 35,000 department stores.            Keywords: Clothes; Prediction; Sales; WMA Method  Abstrak: Toko serba 35.000 adalah usaha yang bergerak dalam bidang penjualan baju yang beralamat di jalan Sisingamangaraja. Baju merupakan salah satu kebutuhan pokok manusia untuk melindungi, dan mempercantik diri. Permasalahan yang terjadi pada toko serba 35.000 adalah Sulitnya memprediksi jumlah penjualan baju, sehingga mengakibatkan terjadinya penumpukkan barang. Metode yang digunakan dalam penelitian ini adalah metode peramalan Weighted Moving Average (WMA). Tujuan penelitian ini adalah untuk menerapkan metode Weighted Moving Average pada sistem peramalan dalam menentukan penjualan baju  pada toko serba 35.000. Hasil penerapan metode Weighted Moving Average untuk memprediksi penjualan baju yang telah dilakukan, maka mendapatkan hasil prediksi bulan juni 2022 dengan menggunakan 3 bobot berjumlah 203 Pcs dengan akurasi kesalahan 33,40% dan hasil prediksi bulan juni 2022 dengan menggunakan 6 bobot berjumlah 220 Pcs dengan akurasi kesalahan 34,31%. Kesimpulan yang diperoleh bahwa metode Weighted Moving Average dapat  memprediksi penjualan baju pada toko serba 35.000 dengan akurat. Kata kunci: Baju; Metode WMA; Penjualan; Prediksi